INTERCULTURAL ASPECTS OF ARTISTIC TRANSLATION - Nazarova Ra’no Rahimovna; O’lmasova Nodira Mashrabovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article is dedicated to the observe of the trouble of figuring out equivalence withinside the translation of phrases from one language to another. The article gives examples of English and Uzbek standards that aren't equal in each languages and are defined through country wide-cultural, ancient and geographical features. The creator indicates a brand new manner of translating such non-equal phrases and ideas from one language to another. The article attracts essential conclusions approximately the idea and exercise of translation and is used to gain correct and powerful translation. The theoretical a part of the observe has been confirmed through many examples.